Prenatal histomorphological changes of cervix in the Surti buffalo - BAISHYA, G; VYAS, K N; KALITA, H C (The Indian Journal of Animal Sciences, 2013)
Cervices from clinically healthy Surti buffalo foetuses (39) were studied at 6 different phases of prenatal life, ranging from 67 to 305 days (8.5 to 102.5 cm CVR). The first evidence of formation of the cervil( was observed in 67 days (8.5 cm CVR) foetus where 2 Milllerian tubes were fused together, caudally to form a common tubular structure which developed into the cervix. It was lined by tall, columnar epithelium at this stage. The primary, secondary and tertiary cervical mucosal folds appeared at 85 days (12.0 cm CVR), 94 days (14.5 cm CYR) and 130 days (25.0 em CVR) foetuses respectively. The average number, height and Width of primary cervical mucosal folds increased with,age. A large primary mucosalsubmucosal fold was noticed at 126 days (23.2 cm CVR) as precursor of future annular ring of cervix.Cerv,ical lining epithelium varied from pseudostratified to simple coiuP1nar epithelium with secretory evidence at 274 days (89.0 cm CVR) onwards. Cervical glands were observed in 143 days (31.0 cm CVR) foetus. Muscularis and scrosal layers of the cervix developed simultaneously in 94 days (14.5 cm CVR) stage and fully developed by 166 days (41.0 cm CVR) foetus. The average thickness of cervical tunics revealed an increasing trend with the advancing gestational ages. However, the average thickness of cervical epithelium was variable.